(untitled) - Lourens, Darrian Brett

Determining the function of MtAMA1, an AGP suspected to play a role in the symbiosis between Medicago truncatula and arbuscular mycorrhizal fungi (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.